1993
DOI: 10.1038/bjc.1993.412
|View full text |Cite
|
Sign up to set email alerts
|

Acetylsalicylic acid (ASA) protects the prostaglandin-cAMP-system of human hypernephroma cells against irradiation-induced alterations

Abstract: Summary There is abundant evidence that inhibitors of prostaglandin (PG) 3.6nM; PGI2: Bmax = 325 ± 194 fmol mg-protein, Kd = 6.8 ± 7.1nM) were significantly (P < 0.01) diminished.However, irradiation had no significant effect on PG bindig sites in ASA-pretreated cells (PGEI:Bmax =699 ± 240fmolmg-protein, Kd = 3.5 + 1.8nM; iloprost: Bmax = 766 ± 452 fmol mg-' protein, Kd = 3.2 ± 2.2nM). Although there was no significant difference in the basal values for cAMP between control and ASA-treated group cells, the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Phorbol esters were included in the media to support viability. Previous studies have shown that endogenously produced PG may downregulate EP receptors (Hashimoto et al, 1991;Li et al, 1993) which could diminish the effect of exogenous PG on dendricity. We therefore first assessed the endogenous production of PGE 2 and PGF 2a in human melanocytes grown in growth factor depleted medium.…”
Section: Resultsmentioning
confidence: 99%
“…Phorbol esters were included in the media to support viability. Previous studies have shown that endogenously produced PG may downregulate EP receptors (Hashimoto et al, 1991;Li et al, 1993) which could diminish the effect of exogenous PG on dendricity. We therefore first assessed the endogenous production of PGE 2 and PGF 2a in human melanocytes grown in growth factor depleted medium.…”
Section: Resultsmentioning
confidence: 99%
“…11,14 In initial experiments, the time course of association of binding was studied by incubating intact cells ( 121 or increasing concentrations (0.001-1000 nM) of other peptides (VIP, SST-14, TNF-␣, EGF and IGF-I). After incubation, the reaction mixture was diluted 1:10 with assay buffer (4°C) and rapidly centrifuged (5,000 g, 10 min, 4°C) to separate membrane-bound from free ligand.…”
Section: In Vitro Binding Studiesmentioning
confidence: 99%
“…Previous reports have suggested that loss of prostaglandin E receptor radioligand-binding activity is associated with more advanced malignancy. 33,[35][36][37] Moreover, treatment of metastatic murine mammary tumor cells with PGE 2 receptor antagonists leads to decreased PGE 2induced cAMP production and increased lung metastasis. 47 We demonstrate that loss of EP 2 receptors in an immortalized, but nontumorigenic human keratinocyte cell line (HaCat) results in increased invasiveness in an organ culture model.…”
Section: Discussionmentioning
confidence: 99%
“…30 -34 Several reports have demonstrated decreased radiolabeled PGE 2 -binding sites by Scatchard analysis in human and rat breast cancer cell lines and hepatocellular carcinoma. [35][36][37] This decreased receptor binding activity led Li and colleagues 33 to propose that the increased prostaglandin production in malignancy might result in prostaglandin receptor down-regulation. Thus, ligand-dependent receptor down-regulation might represent a possible mechanism for the effects of PGE 2 in malignant progression.…”
mentioning
confidence: 99%